Experiences of Non-ICU Nurses’ Redeployment in ICU during Covid-19 Pandemic - Huda A. Mhawish, Faisal A. Alaklobi, Mohammad Alodat, Amany Abdullah Aseere, Batla Alshammari, Badryah Alshehri, Basel Hamid Almuabbadi, Kriz Louie Odchigue, Bobby Rose Marasigan, Abdullah S. Aldamaeen, Ahmed F. Mady, Rayan Alshayeh (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Staff that were redeployed from different departments to the intensive care unit (ICU) dealing with COVID-19 infected patients have had social, psychological, and physical effects as a result of the COVID-19 pandemic. Objective: To evaluated the challenges and experiences of the non-ICU nursing staff when they were redeployed during the current pandemic. Study Design: Place and Duration of Study: Riyadh Healthcare from 1st July 2021 to 31st December 2021 Methodology: Two hundred and thirty-eight respondents were enrolled. Results: 70.6% of redeployed staff claimed very satisfied with neutral behaviour. 80.7% of nurses had the choice before redeployment, and 33.6% of staff felt happy to be redeployed to the ICU. 26.9% were neutral, while only 16.8% of nurses reported feeling very unhappy. Orientation was attended by 81.5% of staff, 54.6 % found it uses full. 50% of participants said they had the same workload as their previous departments, but only 5% of staff complained about a lot more work. The attitude of ICU staff and appreciation of administration showed positive answers compared to complaints in this regard (44.4 and 51.5% positive answers respectively). 63.1% of staff was clear about their role when redeployed to ICU. 47.1% of staff was satisfied, 23.5% remained neutral and 5.9% were dissatisfied with the redeployment. 45.4% claimed their redeployment was useful from a patient care perspective. 83.2% of nurses found new acquaintances useful in ICU and get good support from them. Conclusion: Several factors can contribute to nurses’ dissatisfaction with their redeployment from non-ICU areas, according to this study, including increased workload, poor orientation, a lack of hospital and ICU staff cooperation, and their preferences for where they should work. For the sake of avoiding such issues in the future, these regions must be organized properly. When faced with a pandemic of COVID-19, the healthcare system must be ready with creative solutions that can be applied in a practical situation.